FOMOWA Fishing Records fonds (1915)
323 photographs : sepia toned 8 x 13.5 cm or smaller Title from album caption. The FOMOWA Fishing Club was started in the spring of 1914. The original members were Walter Stanley Monroe, Samuel J. Foote, William Robertson Warren, J. Morey and R. Watson. On July 11, 1914 the members purchased the house and land belonging to John Cormier at Forks Pool on the Grand River, Codroy. The name for the club was suggested by Walter Stanley Monroe. The name being coined by taking the first two letters of the names Forks, Foote, Monroe, Morey, Watson and Warren to form the name FOMOWA. In June 1915, R. Watson expressed his desire to dissolve his share and substituted the name of Samuel F. Milley as the purchaser. A member is often named as the 'president' in captions that accompany a photograph. This refers to the member who has caught the largest salmon and they remain the 'president' until a member catches a salmon that is larger. There were no records kept for 1914. An album containing 323 black and white photographs and 25 pages of text, covering the years 1914 to 1937 of the FOMOWA Fishing Club on the Grand Codroy River on the west coast of Newfoundland. The album's images have been digitized as separate items.